The importance of surgery in scalp angiosarcomas. (December 2018) - Cassidy, Richard J.; Switchenko, Jeffrey M.; Yushak, Melinda L.; Madden, Nicholas; Khan, Mohammad K.; Monson, David K.; Beitler, Jonathan J.; Landry, Jerome C.; Godette, Karen D.; Gillespie, Theresa W.; Patel, Kirtesh R.
Abstract: Background: Scalp angiosarcomas (SA) are rare, representing <1% of soft tissue sarcomas. The optimal management of these tumors is unknown, with management based on small case series. We sought to assess the impact of different therapies on overall survival (OS), the practice patterns nationally, and identify factors associated with OS for non-metastatic scalp angiosarcomas. Methods: A prospectively maintained database was used to identify non-metastatic scalp angiosarcomas who received some form of definitive therapy. Logistics regression, Kaplan-Meier, and Cox proportional-hazard models were utilized. Results: A total of 589 patients met study entry criteria with a median follow-up of 4.2 years. The majority (482 patients, 81.8%) had upfront definitive resection and an additional 317 patients (65.8%) received postoperative radiation. Of the 107 patients who didn't have surgery, the majority (65 patients, 60.7%) received definitive radiation and 42 patients (39.3%) received radiation and chemotherapy. One-year and five-year survival estimates for patients not receiving definitive surgery were 68.0% (95%CI: 57.5–76.4) and 18.0% (95%CI: 10.2–27.5) respectively compared to 78.2% (95%CI: 74.0–81.9) and 34.1% (95%CI: 28.9–39.3) for patients receiving definitive surgery (p < 0.01). On multivariable analysis, age ≥65 years, tumor size ≥5 cm, and not receiving definitive surgery was associated with worse OS. Conclusions: The majority of patients with non-metastatic scalp angiosarcomas had upfront definitive surgery, with a subsequent improvement in OS, including when accounting for other patient and tumor factors. Postoperative radiation was frequently given. Our large series confirmed age and tumor size as prognostic factors for this rare disease.